Exploring the Influence of Failure Aversion on Learning From Project Failure: A Sensemaking Perspective - Zhang, Liangting; Wang, Bin; Feng, Xiaoxia; Zhang, Yue; Wang, Wenzhou (Frontiers in Psychology, 2022)
Although project failure is commonly considered a negative event, it can provide valuable resources for learning. Despite well documented research on the antecedents of learning from project failure at the individual level, individuals’ attitude toward failures, a relatively proximal antecedent of learning from failure, has attracted limited attention in organizational studies. To address this paucity of research, based on the sensemaking theory, in the current study we specifically focused on individuals’ failure aversion and explored how it would influence learning from failure through the process of arguing and expectation. Using a sample of 774 employees from R&D teams in China, our findings revealed that individuals’ failure aversion enhanced their learning from failure through inducing a loss-focused coping, but failure aversion negatively affected learning from failure through increasing the individuals’ perceived loss of self-esteem. We also found that individuals’ learning goal orientation weakened the negative relationship between the loss of self-esteem and learning from failure; however, individuals’ learning goal orientation did not moderate our hypothesized relationship between loss-focused coping and learning from failure. Our study extends the literature on learning from failure in two ways. First, it explores the learning from failure process at the individual level based on the sensemaking theory and second, it sheds light on the underlying cognitive underlying mechanisms operating between failure aversion and learning from project failure.